Role of mid-size corporate travel agencies in Singapore : a case study on diners world travel. - Chan, Jocelyn Gek Ching. (2008)
We attempt to examine the role of the mid-size travel agencies in Singapore, on the aspects of technology, service attributes, service fees and direct selling. Specifically, we study the perceptive differences among three parties, namely corporate clients, operational staff and management, by using the case study method, with corporate travel as our main focus, as it is an area largely unexplored.